Electromagnetic compatibility of multifunctional automation systems for electrical equipment using the example of electric drives - Kryukov, Oleg; Saushev, Alexander; Shergina, Olga; Butsanets, Artem (E3S web of conferences, 2021)
The main factors of information compatibility of automatic control systems for energy-saving electric drives are proposed, built on the basis of multifunctional algorithms, when integrated into a single information space of an enterprise. The method for assessing compatibility allows one to purposefully vary the specific shares of data storage and processing processes in the software, as well as to solve the problems of computer modeling and the choice of identification and adaptation algorithms in the general cycle of work. The indicators of the systems operability are given – the coefficients of increasing the productivity of software modules, the essence of the subject area, the accuracy of assessing the input and output information, the probability of achieving the goal, the times of transient processes during information exchange, depending on information resistance, rigidity, memory volume and the level of information-driving logic. It is shown that this will allow avoiding the influence of reactive parameters of information circuits in control systems.